Conversion of Biomass Derivatives to Electricity in Photo Fuel Cells using Undoped and Tungsten‐doped Bismuth Vanadate Photoanodes. Issue 23 (24th November 2015) - Zhang, Bingqing; Shi, Jingying; Ding, Chunmei; Chong, Ruifeng; Zhang, Bao; Wang, Zhiliang; Li, Ailong; Liang, Zhenxing; Liao, Shijun; Li, Can
Abstract: The photo fuel cell (PFC) is a promising technology for simultaneously converting solar energy and bioenergy into electricity. Here, we present a miniature air‐breathing PFC that uses either BiVO4 or W‐doped BiVO4 as the photoanode and a Pt/C catalyst as the air‐breathing cathode. The PFC exhibited excellent performance under solar illumination and when fed with several types of biomaterial. We found the PFC performance could be significantly enhanced using W‐doping into the BiVO4 photoanode. With glucose as the fuel and simulated sunlight (AM 1.5 G) as the light source, the open‐circuit voltage increased from 0.74 to 0.92 V, the short‐circuit current density rose from 0.46 to 1.62 mA cm −2, and the maximum power density was boosted from 0.05 to 0.38 mW cm −2, compared to a PFC using undoped BiVO4 as the anode. Abstract : The power of tungsten doping : Photo fuel cells with BiVO4 and tungsten‐doped BiVO4 as the photoanode exhibited excellent performance toward conversion of various biomass derivatives into electricity under AM 1.5 G simulated sunlight. The tungsten‐doped photoanode led to increases in both open‐ circuit voltage and short‐circuit current density compared to undoped BiVO4, yielding a 0.33 mW cm −2 increase in the maximum power density of the cell.